The GALAH Survey: improving our understanding of confirmed and candidate planetary systems with large stellar surveys. Issue 2 (2nd December 2021) - Clark, Jake T; Wright, Duncan J; Wittenmyer, Robert A; Horner, Jonathan; Hinkel, Natalie R; Clerté, Mathieu; Carter, Brad D; Buder, Sven; Hayden, Michael R; Bland-Hawthorn, Joss; Casey, Andrew R; De Silva, Gayandhi M; et al.
ABSTRACT: Pioneering photometric, astrometric, and spectroscopic surveys is helping exoplanetary scientists better constrain the fundamental properties of stars within our galaxy and the planets these stars host. In this study, we use the third data release from the stellar spectroscopic GALAH Survey, coupled with astrometric data of eDR3 from the Gaia satellite, and other data from NASA's Exoplanet Archive, to refine our understanding of 279 confirmed and candidate exoplanet host stars and their exoplanets. This homogenously analysed data set comprises 105 confirmed exoplanets, along with 146 K2 candidates, 95 TESS Objects of Interest (TOIs), and 52 Community TOIs (CTOIs). Our analysis significantly shifts several previously (unknown) planet parameters while decreasing the uncertainties for others. Our radius estimates suggest that 35 planet candidates are more likely brown dwarfs or stellar companions due to their new radius values. We are able to refine the radii and masses of WASP-47 e, K2-106 b, and CoRoT-7 b to their most precise values yet to less than 2.3 per cent and 8.5 per cent, respectively. We also use stellar rotational values from GALAH to show that most planet candidates will have mass measurements that will be tough to obtain with current ground-based spectrographs. With GALAH's chemical abundances, we show through chemo-kinematics that there are five planet hosts that are associated with the galaxy's thick disc, including NGTS-4, K2-183, and K2-337. Finally, we show that there is no statistical difference between the chemical properties of hot Neptune and hot rocky exoplanet hosts, with the possibility that short-period rocky worlds might be the remnant cores of hotter, gaseous worlds.